PENGARUH IKLIM ORGANISASI DAN PEMBERDAYAAN TERHADAP KEPUASAN KERJA MELALUICAREER PLATEAU (STUDI PADA SEKRETARIAT DAERAH KABUPATEN PATI) - FendyEko Sulistianto, 1352020080 (Jurnal Mahasiswa Pasca Sarjana, 2015)
This study aimstoexamineandanalyzethe influence oforganizational climateandempowermenton thejob satisfaction through career plateau.Analysistoolused ismultiple regression, as fortesting the hypothesisusinga t test. Data collectionthroughquestionnairestomeasureusingLikertscaleof 7 (seven) alternativeanswers. Object of researchis employees at Sekretariat Daerah in Pati regency. Number of samplesin this study were111respondents. Samplingtechniqueusing thepurposive sampling. The results showed that(1)Organizational climatehave a negative and significant impact oncareer plateau, (2)Empowermenthave a negative and significantimpact oncareer plateau, (3)Organizational climatehave a positive and significant impact onjob satisfaction, (4)Empowerment have a positive and significantimpact onjob satisfaction, (5 ) Career plateauhave not effecton job satisfaction, (9)career plateau does not mediatetheeffect oforganizational climate on job satisfaction (10)career plateau does notmediate theeffect ofempowermenton job satisfaction. Keywords: Organizational Climate, Empowerment, Career Plateau and job satisfaction